Dimensi Carter dalam Peningkatan Kualitas Layanan dan Loyalitas Nasabah pada PT. BPRS Bhakti Sumekar Cab. Pragaan - Siti Inayatul Azaliya; Holilur Rahman (Universitas Muhammadiyah Surabaya, 2026)
The quality of service provided by the bank is one of the factors that can attract customers. To find out how much quality of service in Islamic banking, you can use the CARTER dimensions, namely Compliance, Assurance, Reliability, Tangible, Empathy, and Responsiveness. However, there are still complaints from customers regarding the quality of service that is not optimal. Starting from the parking facilities that are still minimal and the assumption that BPRS does not provide ATM facilities. The problem raised in this study is how the quality of service and customer loyalty at BPRS Bhakti Sumekar Cab. Pragaan by using the CARTER dimension, which is described in two focuses, namely: 1. How is the application of the CARTER dimension at PT BPRS Bhakti Sumekar Cab. Pragaan 2. How the CARTER dimension can improve service quality and customer loyalty at PT BPRS Bhakti Sumekar Cab. Pragaan. This research was designed using a descriptive qualitative approach. The data sources in this research are branch heads, tellers, and customers. The data collection techniques used were observation, interviews, and documentation. Data analysis uses data reduction, data presentation, and conclusion drawing. For data validity, researchers used observation persistence and triangulation. The results of this study are the implementation of the CARTER dimension that has been carried out at PT. Bank BPRS Bhakti Sumekar Cab. Pragaan has been implemented well, this can be seen from customer satisfaction with the services provided both in terms of compliance with sharia, guarantees, reliability, physical evidence, concern and responsiveness. CARTER dimensions can improve service quality and customer loyalty at BPRS Bhakti Sumekar Cab. Pragaan, this can be seen from employees when providing services to customers. While customer loyalty is seen from customers making repeated purchases, customers recommending to others, talking about positive things to others and showing immunity to the pull of competitors.